Growing Pains from Rapid Growth: A Historical Case Study of George Fox University from 1983 to 2003 - Railsback, Gary L. (Christian higher education, 2007)
This article is a historical case study of George Fox University (GFU) in Newberg, Oregon. Using organizational lifecycle as a theoretical framework, George Fox University had a long and delayed childhood in that it remained a small and struggling institution for most of the 20th century, and then experienced rapid growth in the late 1980s. This qualitative research project involved interviews with 72 current and former faculty and administrators that worked at the university during this time of rapid growth. Findings are that growth was attributed to five major reasons: (a) the entrepreneurial style of the president; (b) new marketing and recruitment strategies; (c) development of new undergraduate programs; (d) development of graduate programs; and (e) mergers and acquisitions. Implications of these findings for other Christian colleges are discussed with qualifications focused around geographic location near a major metropolitan area, demographics of high school graduates and adults seeking graduate programs, and lessons learned from mergers and acquisitions.